2017
DOI: 10.1021/acs.jpcc.7b05429
|View full text |Cite
|
Sign up to set email alerts
|

Ductility in Crystalline Boron Subphosphide (B12P2) for Large Strain Indentation

Abstract: Our studies of brittle fracture in B 4 C showed that shear induced cracking of the (B 11 C) icosahedra leading to amorphous B 4 C regions induced cavitation and failure. This suggested that to obtain hard boron rich phases that are ductile, we need to replace the CBC chains of B 4 C with two-atom chains that can migrate between icosahedra during shear without cracking the icosahedra. We report here quantum mechanism (QM) simulation showing that under indentation stress conditions, superhard boron subphosphide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
(103 reference statements)
2
23
0
Order By: Relevance
“…With the intent of mitigating the adverse effects of amorphization in B 4 C subjected to shear loading, we used QM to examine substitutions of these CBC chains with two atom chains such as Si-Si [29], PP [30], OO [31] (note, it has been demonstrated before that the fundamental cause of B 4 C brittle fracture is the reaction of the middle B in the CBC chains). Indeed the QM shows that (B 11 C)(SiSi) and (B 11 C)(PP) leads to very ductile materials, with the single crystal staying stable as the shear is continued to large strains [29,30,31]. Unfortunately the standard techniques for fabricating B 4 C do not lead to incorporating Si-Si chains.…”
Section: Accepted Articlementioning
confidence: 99%
“…With the intent of mitigating the adverse effects of amorphization in B 4 C subjected to shear loading, we used QM to examine substitutions of these CBC chains with two atom chains such as Si-Si [29], PP [30], OO [31] (note, it has been demonstrated before that the fundamental cause of B 4 C brittle fracture is the reaction of the middle B in the CBC chains). Indeed the QM shows that (B 11 C)(SiSi) and (B 11 C)(PP) leads to very ductile materials, with the single crystal staying stable as the shear is continued to large strains [29,30,31]. Unfortunately the standard techniques for fabricating B 4 C do not lead to incorporating Si-Si chains.…”
Section: Accepted Articlementioning
confidence: 99%
“…Several approaches, such as microalloying [12][13][14][15][16] , stoichiometry control [17][18][19] , and addition of a 2 nd phase [20][21][22] , have been proposed to mitigate amorphous shear band formation. For microalloying, both non-metal dopants (P 23 and Si 24 ), as well as metal dopants (Li 14,15 , Mg 12,16 , and Ti 13 ) may decrease amorphization in B 4 C. Both experimental and theoretical studies have suggested…”
Section: Introductionmentioning
confidence: 99%
“…Boron carbide (B 4 C) is the leading candidate for a neutron absorber for next-generation fast reactors, which are entrusted with the important task of providing sustainable nuclear energy [1,2]. However, due to the helium gas produced from the 10 B[n, α] 7 Li reaction, the volume swelling of the B 4 C pellets during use has been a critical safety issue for the longterm use of the control rods [3][4][5]. Moreover, the brittleness of B 4 C makes the pellets very easy to break into small fragments under the internal stress induced by the heat gradient and helium gas production.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this change is to avoid partial amorphization of the B 4 C grains under stress by enhancing the slip between the boron icosahedra. A series of investigations based on DFT calculations of (B 11 C p )Si 2 , (B 10 Si 2 )Si 2 , B 12 P 2 , and B 12 O 2 revealed that these compounds with two-atom chains instead of three-atom chains are not likely to form amorphous bands under stress, which normally lead to brittle failure [6][7][8][9]. Compared to B 4 C, these materials have similar boron content and improved ductility characteristics, and are therefore expected to outperform B 4 C as neutron absorbers for fast reactors by reducing the pellet fragmentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation